The smallest things make me emotional! Emotion reactivity in non-suicidal self-injury: trait, state, and physiological differences - Jankowski, Melissa S.; Legasse, Aubrey J.; Marques, Victoria; Delcourt, Meaghan L.; Haigh, Emily A. P. (Frontiers in Psychology, 2024)
Objective: The current study sought to clarify the role of emotion reactivity in non-suicidal selfinjury (NSSI) by examining three forms of emotion reactivity (physiological and self-reported trait and state reactivity) among a sample of young adults with or without a history of NSSI.Materials and Methods: Seventy-six adults (Mage = 20.97, 73.7% female) participated in a semi-structured clinical interview to determine NSSI history and completed a measure of trait emotion reactivity. Participants then provided state emotion reactivity ratings before and after a social rejection task, recovery period, and positive mood induction while physiological data was continuously recorded.Although individuals with a history of NSSI perceived themselves to be more emotionally reactive, these participants were not more physiologically reactive, nor were their state reactivity ratings significantly different from individuals without a history of NSSI.Discussion: Results suggest increased emotionality in response to a stressor is within normal bounds and not unique to individuals with a history of NSSI, and provide implications for future research on the etiology and treatment of NSSI.